Total quality a manager's guide for the 1990s (Kogan page, 1992)
Quality is becoming the new standard for running a successful business in the 1990s. This text offers managers a succinct yet comprehensive guide to adopting this new philosophy of doing business. The book describes not only what the manager must know but also what he or she must do to help accomplish the radical changes needed to ensure competitive superiority. It aims to provide detailed assistance on the following topics: how to develop leadership commitment; policy deployment - managing change at all levels in a company; measuring and rewarding performance; education and training requirements; just-in-time and quality; building world-class suppliers; and implementing the right levels of technology and automation. The book aims to take the confusion and mystery out of establishing and running an effective quality improvement programme in any organization.